2017
DOI: 10.1111/pce.13044
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar processing enzyme activates programmed cell death in the apical meristem inducing loss of apical dominance

Abstract: The potato (Solanum tuberosum L.) tuber is a swollen underground stem that can sprout in an apical dominance (AD) pattern. Bromoethane (BE) induces loss of AD and the accumulation of vegetative vacuolar processing enzyme (S. tuberosum vacuolar processing enzyme [StVPE]) in the tuber apical meristem (TAM). Vacuolar processing enzyme activity, induced by BE, is followed by programmed cell death in the TAM. In this study, we found that the mature StVPE1 (mVPE) protein exhibits specific activity for caspase 1, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
(109 reference statements)
2
21
0
Order By: Relevance
“…Following the stress, induction of StVPE1 in the stem meristem induces loss of apical dominance and stem branching. The mature StVPE1 protein exhibits specific activity for caspase-1, with optimal activity at acidic pH, consistent with its established vacuolar localization (Teper-Bamnolker et al, 2017). Downregulation of St VPE1 by RNA interference (RNAi) or overexpression of green fluorescent protein-labeled StVPE1 ( StVPE1-GFP ) results in reduced or enhanced stem branching, respectively (Teper-Bamnolker et al, 2017).…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…Following the stress, induction of StVPE1 in the stem meristem induces loss of apical dominance and stem branching. The mature StVPE1 protein exhibits specific activity for caspase-1, with optimal activity at acidic pH, consistent with its established vacuolar localization (Teper-Bamnolker et al, 2017). Downregulation of St VPE1 by RNA interference (RNAi) or overexpression of green fluorescent protein-labeled StVPE1 ( StVPE1-GFP ) results in reduced or enhanced stem branching, respectively (Teper-Bamnolker et al, 2017).…”
Section: Introductionsupporting
confidence: 54%
“…VPE is considered a PCD executor in plant systems in response to several biotic and abiotic stresses (reviewed by Hatsugai et al, 2015; Vorster et al, 2019). Phylogenetic analysis has shown that StVPE1, classified as a vegetative-type VPE, has high sequence similarity and conserved regions with tobacco NtVPE-1a , NtVPE-1b , NtVPE-2 and NtVPE-3 (Teper-Bamnolker et al, 2017; Supplementary data 1A). To study its role in PCD induction, VPE-RNAi-expressing BY-2 lines were produced, and their PCD response was compared to that in wild-type (WT) cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations